Separate medication preparation rooms reduce interruptions and medication errors in the hospital setting: a prospective observational study - Huckels-Baumgart, Saskia; Baumgart, André; Buschmann, Ute; Schüpfer, Guido; Manser, Tanja (Journal of patient safety, 2021)
Background: Interruptions and errors during the medication process are common, but published literature shows no evidence supporting whether separate medication rooms are an effective single intervention in reducing interruptions and errors during medication preparation in hospitals. We tested the hypothesis that the rate of interruptions and reported medication errors would decrease as a result of the introduction of separate medication rooms. Aim: Our aim was to evaluate the effect of separate medication rooms on interruptions during medication preparation and on self-reported medication error rates. Methods: We performed a preintervention and postintervention study using direct structured observation of nurses during medication preparation and daily structured medication error self-reporting of nurses by questionnaires in 2 wards at a major teaching hospital in Switzerland. Results: A volunteer sample of 42 nurses was observed preparing 1498 medications for 366 patients over 17 hours preintervention and postintervention on both wards. During 122 days, nurses completed 694 reporting sheets containing 208 medication errors. After the introduction of the separate medication room, the mean interruption rate decreased significantly from 51.8 to 30 interruptions per hour (P < 0.01), and the interruption-free preparation time increased significantly from 1.4 to 2.5 minutes (P < 0.05). Overall, the mean medication error rate per day was also significantly reduced after implementation of the separate medication room from 1.3 to 0.9 errors per day (P < 0.05). Conclusions: The present study showed the positive effect of a hospital-based intervention; after the introduction of the separate medication room, the interruption and medication error rates decreased significantly.
Gesehen am 15.07.2021